COVID-19 and mucormycosis superinfection: Exploring the missing pathophysiological links. (August 2021) - Almas, Talal; Nazar, Waqas; Khedro, Tarek; Kanawati, M. Ali; Adnan, Alishba; Almuhaileej, Mohammad; Alshamlan, Abdulaziz; Abdulhadi, Abdulaziz; Manamperi, Kuvira T.; Sarfraz, Saba
Abstract: The coronavirus disease 2019 continues to unearth new facets that portend grave clinical implications. In recent times, there has been mounting fervor regarding coronavirus disease 2019 and mucormycosis superinfection. While the correlation between the two is conspicuous, the underlying pathophysiological mechanisms that render a patient with coronavirus disease 2019 susceptible to mucormycosis, or vice versa, are still elusive. Highlights: In recent times, there has been mounting fervor regarding coronavirus disease 2019 and mucormycosis superinfection. While the correlation between the two is conspicuous, the underlying pathophysiological mechanisms that render a patient with coronavirus disease 2019 susceptible to mucormycosis, or vice versa, are still elusive. Coupled with the urgent need to treat the cytokine storm via immunosuppressive steroids, the resultant host condition provides an optimal environment for the fungus to thrive.